Exploring the challenges confronting girls in pursuing formal education as perceived by adults - Sulaimon, Jamiu Temitope; Oluwafemi, Folarin Moruf; Shuiabu, Garba; Yakubu, Francis Moodu; khosiyono, Banun Havifah Cahyo; Widyastuti, Ima; Uchechukwu, Kalu (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
This study examines exploring the challenges confronting girls in pursuing formal education as perceived by adults in Dutsinma Local Government, Katsina State. The population for this comprised all Adults in Dutsinma Local Government, Katsina State. Ten (10) villages were selected across the Dutsinma Local Government. based on the researcher’s interest, and a total number of three hundred (300) adults were selected as the sample size for this study using a simple random sampling technique. The test re-test reliability method was used to determine the validity and reliability of the instrument using Pearson product-moment correlation (PPMC) and a co-efficient of 0.73 was established. The research questions and hypothesis raised for this study were analyzed using descriptive statistics such as mean and standard deviation and (ANOVA). The findings from this study showed that the lack of money, which is a consequence of marrying early and getting pregnant, results in girls not being able to study, Distance of schools and depleted school infrastructures, war outbreak and their family’s social status as well as their own personal choice of falling in-love than prioritizing their studies resulted to girl’s poor access to formal education. Also resolving Challenges confronting Girl Child/women access to formal Education, government needs to Enacting laws that make educating the girl-child mandatory, And the hypothesis tested revealed that there was a significant difference parent’s perception on the Challenges confronting Girls in Pursuing Formal Education in Dutsinma Local Government, Katsina State based on educational Qualification.